The Role of Artificial Intelligence in Information Systems (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article identifies digitalization programs that are being implemented in different countries, lists the advantages and disadvantages that digital transformation gives to the economy. The impact of digitalization on the labor market is described: on the one hand, it leads to an increase in unemployment, and on the other, it implies an increase in employment due to the emergence of new professions. Statistics on unemployment in some countries are provided. Professions that may disappear due to the digitalization of the economy and that may become in demand are indicated.